A256 COMPARING GLOBAL OUTCOMES FOR ENDOSCOPIC SUBMUCOSAL DISSECTION: A SYSTEMATIC REVIEW AND META-ANALYSIS. (1st March 2018) - Daoud, D; Suter, N; Durand, M; Bouin, M; Faulques, B; Barkun, A N; von Renteln, D
Abstract: Background: Endoscopic submucosal dissection (ESD) has become the preferred approach to remove advanced gastrointestinal lesions in Asian countries while widespread adoption in the Western world remains limited. Studies evaluating differences for ESD outcomes between Eastern and Western countries are lacking. Aims: To provide a comprehensive review on outcomes of ESD between different regions. Methods: A systematic review and meta-analysis was performed using PubMed, MEDLINE, Web of Science, CINAHL and EBM reviews to identify studies published between 1990 and February 2016. The primary outcome was the efficacy of ESD based on information about either curative resection, en bloc, or R0 resection rates. Secondary outcomes were complication rates, local recurrence rates and procedure times. Results: Overall, 241 publications including 86 388 patients and 91 582 gastrointestinal lesions resected using ESD were identified. 90% of the identified studies reporting ESD on 89 283 lesions were conducted in Eastern countries and 10% of the identified studies reporting ESD outcomes in 2 289 lesions were from Western countries. Meta-analyses showed higher pooled percentage of curative, en bloc, and R0 resection in the Eastern studies; 82% (CI: 81–84), 95% (CI: 94–96) and 89% (CI: 88–91) compared to Western Studies; 71% (CI: 61–79), 85% (CI: 81–89) and 74% (CI: 67–81) respectively. The percentage of perforation requiring surgery was significantly greater in the Western countries (0.49%; CI: 0.09–1.08) compared to Eastern countries (0.02%; CI 0-0, 05). ESD procedure times were longer in Western countries (110 vs 77min). Conclusions: Eastern countries show better ESD outcomes compared to western countries. Availability of local ESD expertise and regional outcomes should be considered for decision making to treat gastrointestinal lesions with ESD. Funding Agencies: None